Frequency adaptive learning SOFM for grayscale image compression - Tan, Chiang Poo. (2008)
A new learning algorithm is proposed where the learning constant is based on the localized winning frequency of each individual neuron. Blocks of sub-image are fed in a butterfly-jumping sequence during the training process. Untrained neurons are also re-initialized.